COMMUNITY EMPOWERMENT IN UTILIZING SALAK FRUIT WASTE BY ADOPTING CREATIVE ECONOMIC INDUSTRY IN SITARATOIT VILLAGE - Delima Sari Lubis; Rini Hayati; Nur Mutiah; Risna Hairani; Replita; Aliman Syahuri Zein; Sri Meylinda (RADJA PUBLIKA, 2024)
Salak (Salacca Zalacca) is a tropical fruit horticultural commodity native to Indonesia. It has important nutritional content and benefits for the human body, one of the central areas of salak production in Indonesia is Sitaratoir Village which is located in the West Angkola sub-district of South Tapanuli Regency, North Sumatra Province. Based on data from BPS (Central Statistics Agency), salak production in the West Angkola sub-district is 319,907 quintals (kw), the high amount of salak production makes the area export to other areas in the form of fresh fruit. The weakness of this salak fruit is that it rots easily so it cannot be reused, coupled with the inability of the surrounding community to process salak fruit waste into something of economic value. Therefore, efforts are needed to recycle salak waste based on the creative economy industry through Community Service (PKM). This activity aims to increase the potential of salak waste through utilization into environmentally friendly floor cleaner products as an effort to improve the welfare of the local community. This activity is carried out in several stages, the first is to establish cooperation with local government officials, the second stage is to conduct preliminary tests on product manufacturing, socialization and finally assistance in product processing in the community. The output produced in this PKM activity is a floor cleaner product which is then published in the form of a journal or published in print media.